Evaluation of a Family-Based Intervention Program for Children of Mentally Ill Parents: Study Protocol for a Randomized Controlled Multicenter Trial - Wiegand-Grefe, Silke; Filter, Bonnie; Busmann, Mareike; Kilian, Reinhold; Kronmüller, Klaus-Thomas; Lambert, Martin; Norra, Christine; von Klitzing, Kai; Albermann, Kurt; Winter, Sibylle Maria; Daubmann, Anne; Wegscheider, Karl; et al. (Frontiers in Psychiatry, 2021)
Background: Children of mentally ill parents have a three to seven times higher risk of developing mental disorders compared to the general population. For this high-risk group, specialized prevention and intervention programs have already been developed. However, there has been insufficient sytematic evaluation to date. Moreover, effectiveness and the cost-effectiveness data of the respective programs until today is very scarce and at the same time constitutes the pre-condition for the program's implementation into regular health care. Methods: The study consists of a two-group randomized controlled multicenter trial conducted at seven study sites throughout Germany and Switzerland. Participants are families with mentally ill parents and their children aged from 3 to 19 years. The intervention comprises 6 to 8 semi-structured sessions over a period of about 6 months. Topics discussed in the intervention include parental mental illness, coping, family relations and social support. Families in the control condition will receive treatment as usual. The children's mental health, assessed using the K-SADS-PL by blinded external raters will constitute the primary efficacy outcome. Further outcomes will be assessed from the parents' as well as from the children's perspectives. Participants are investigated at baseline, 6, 12, and 18 months after baseline assessment. In addition to the assessment of various psychosocial outcomes, a comprehensive health-economic evaluation will be performed. Discussion: This paper describes the evaluation of a family-based intervention program for children of mentally ill parents (CHIMPs) in the regular health care system in Germany and Switzerland. A methodically sophisticated study design has been developed to reflect the complexity of the actual health care situation. This trial will contribute to the regular health care for the high-risk group of children of mentally ill parents. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT02308462; German Clinical Trials Register: DRKS00006806.